2006
DOI: 10.1088/1475-7516/2006/08/009
|View full text |Cite
|
Sign up to set email alerts
|

Inflation after WMAP3: confronting the slow-roll and exact power spectra with CMB data

Abstract: Abstract.The implications of the WMAP (Wilkinson Microwave Anisotropy Probe) third year data for inflation are investigated using both the slow-roll approximation and an exact numerical integration of the inflationary power spectra including a phenomenological modelling of the reheating era. At slow-roll leading order, the constraints ǫ 1 < 0.022 and −0.07 < ǫ 2 < 0.07 are obtained at 95% CL (Confidence Level) implying a tensor-to-scalar ratio r 10 < 0.21 and a Hubble parameter during inflation H/m Pl < 1.3 × … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
374
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 242 publications
(396 citation statements)
references
References 142 publications
(404 reference statements)
17
374
3
2
Order By: Relevance
“…[11,12] (see also subsequent works [13][14][15][16]), the epoch of reheating, the era during which the vacuum energy of the inflaton is converted into * Electronic address: jmartin@iap.fr † Electronic address: christophe.ringeval@uclouvain.be ‡ Electronic address: vincent.vennin@port.ac.uk radiation, impacts the predicted values of the scalar spectral index and tensor-to-scalar ratio for all inflationary models. As a result, reducing uncertainties on the measured values of these two parameters provides some nontrivial information on how reheating proceeds, even if inflation is as simple as a slow-roll single-field scenario [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12] (see also subsequent works [13][14][15][16]), the epoch of reheating, the era during which the vacuum energy of the inflaton is converted into * Electronic address: jmartin@iap.fr † Electronic address: christophe.ringeval@uclouvain.be ‡ Electronic address: vincent.vennin@port.ac.uk radiation, impacts the predicted values of the scalar spectral index and tensor-to-scalar ratio for all inflationary models. As a result, reducing uncertainties on the measured values of these two parameters provides some nontrivial information on how reheating proceeds, even if inflation is as simple as a slow-roll single-field scenario [17].…”
Section: Introductionmentioning
confidence: 99%
“…Within a given model of inflation, predicting the scalar spectral index and tensor-to-scalar ratio requires us to specify a value for the so-called rescaled reheating parameter R reh [11]. More specifically, once R reh is given, one can uniquely determine the number of e-folds before the end of inflation at which an observable mode k * crosses the Hubble radius [18], a quantity which is required to get the actual values of the observed slowroll parameters [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…We found however that in a large part of the parameter space in which a bounce is realized (see Section III), the spectrum of CMB multipoles (Fig. 9) is merely modified in a way reminiscent of superimposed oscillations, a possibility that has attracted some attention in recent years [33], and was found to be not inconsistent with the data. Any oscillations in the matter power spectrum or CMB multipoles are expected to be mostly smoothed out either by transfer functions or observational windowing functions.…”
Section: Discussionmentioning
confidence: 73%
“…This can however be handled by assuming the bounce-making negative energy component to be merely phenomenological, acting only for a short time, the bounce duration, in general assumed comparable with the Planck scale. In any case, there are no generic properties that can be derived in a model-independent way as in slow-roll inflation [33]. Very often, though, it is found that a reasonable model connects two almost de Sitter phases.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently there has been an interesting development [15,19,20] to distinguish various inflationary models by indirectly looking at the possible physically motivated reheating mechanism through the evaluation of a particular observable scale and the entropy density till to- , and equal number of e-folding parameters N re1 = N re2 .The light blue shaded region corresponds to the 1σ bounds on ns from Planck. The brown shaded region corresponds to the 1σ bounds of a further CMB experiment with sensitivity ±10 −3 [17,18], using the same central ns value as Planck.…”
Section: Constraining Through Reheating Predictionsmentioning
confidence: 99%